A Co(ii) complex of a vitamer of vitamin B6 acts as a sensor for Hg2+ and pH in aqueous media. (24th May 2016) - Sing, Nilam; Roy, Sanjay; Guin, Partha Sarathi; Mahali, Kalachand; Majee, Prakash; Mondal, Sudip Kumar; Mahata, Partha; Sengupta, Partha Sarathi; Mondal, Palash
Abstract : A new Co(ii ) complex was prepared by template reaction, acting as a dual fluorescent sensor for Hg 2+ ions and pH in aqueous solution. Abstract : A Co(ii ) complex of molecular formula C48 H96.8 N12 O22.4 Co2 Cl2, 1, was synthesized from the Schiff base [H2 pydmdp]Cl by a template reaction of pyridoxal (pyd), a vitamer of vitamin B6, N -methyl-1, 3-diaminopropane (mdp) and cobalt(ii ) acetate. It was characterized by elemental analysis, 1 H NMR, IR and UV-Vis spectroscopy, thermal analysis, electrochemistry and single crystal X-ray diffraction. The experimental results suggested that in complex 1, the central Co(ii ) is bonded to two phenolato-oxygens, two imine nitrogens and two amine nitrogens in an octahedral geometry. In aqueous media complex 1 exhibits an intense fluorescence emission peak at 506 nm when it was excited at 425 nm. The fluorescence behavior of complex 1 in aqueous media was employed to determine whether it acts as a chemosensor for some selective toxic metal ions. The studies showed that the present complex behaves as a promising sensor for Hg 2+ even at the sub-micromolar level. In addition in aqueous solution, complex 1 acts as a sensor for the pH of the medium. A detailed study on the mechanism of sensing behavior established that Hg 2+ interacts with complex 1 via weak non-covalent interaction with the N-atom of the pyridine moiety of the molecule. The pyridine nitrogen also plays a vital role in sensing the pH of the medium.